To Use “God” or “Allah”? (American Journal of Islam and Society, 2009)
Recently there was a discussion on the American Academy of Religion listserve’s“Islam” section on whether “Allah” is simply a noun or a proper nameof God and whether English-speaking Muslims should use “God” instead of“Allah.” As the majority seemed to agree that “Allah” is Arabic for God, as“Khoda” is in Urdu and Persian, there was no agreement on using “God”instead of “Allah.” But what I did not see discussed was howtheQur’an presentsthe term Allah; after all, it uses this term about 980 times.1 Admittedlythere was one attempt to bring in al-Ghazali’s theological stance, but it waspursued no further than “Allah is God’s proper name.” ...